The effect of hybrid coatings based on hydrogel, biopolymer and inorganic components on the corrosion behavior of titanium bone implants. Issue 43 (9th October 2019) - Saveleva, Mariia; Vladescu, Alina; Cotrut, Cosmin; Van der Meeren, Louis; Surmeneva, Maria; Surmenev, Roman; Parakhonskiy, Bogdan; Skirtach, Andre G.
Abstract : Dependence of variation of Ti bone implant corrosion behavior on the composition of bioactive coating. Abstract : Modification of titanium (Ti) bone implant materials with hybrid organic–inorganic coatings is a novel promising approach to improve the osteoconductivity and osteointegration of implants and prevent their failure after implantation. However, in these coatings, which are mostly hydrophilic, chemically active moieties capable of releasing oxidizing ions can have a significant influence on the corrosion resistance of Ti, which is critical for the Ti implant osteointegration behavior. In this research, in order to study the dependence of the change of the corrosion behavior of Ti on the composition of the coating, Ti surfaces were modified with various coatings: organic (alginate hydrogel crosslinked with Ca 2+ ions (Alg), and dextran sulfate (DS)), inorganic (porous calcium carbonate CaCO3 ), and composite organic–inorganic (Alg-CaCO3, DS-CaCO3 ). The morphology and composition of these materials before and after the corrosion experiment, performed in simulated body fluid (SBF), were followed by extensive characterization. Electrochemical impedance spectroscopy (EIS) was performed to study the corrosion behavior of the prepared materials in SBF. The characteristics obtained during the EIS measurements revealed the dependence of the variation of the corrosion resistance level on the composition of the coating. The bare Ti surface had the higher value of the total impedance compared with the modified surfaces, while the Ti surfaces modified with organic coatings demonstrated the best charge transfer resistance in comparison with the coatings containing the inorganic CaCO3 component and uncoated Ti.